Concept Design and Analysis of a Novel Steamer-Filling Robot - Enhong Xing; Bin Li; Xinhua Zhao (Journal of Robotics)
Steamer-filling operation is a crucially important process in the liquor-making process, directly related to liquor yield and liquor quality. But so far, this process is still dominated by manual operation. In view of working environment and labor shortages in this industry, a novel exclusive steamer-filling robot is proposed in this paper. Firstly, the steamer-filling operation process is described, and the structure composition and function realization of the robot are particularly introduced. Secondly, the kinematics problems in terms of position analysis and workspace of the robot are analyzed in detail. Thirdly, experimental analyses are made to prove the validity and efficiency of the robot system. Finally, some conclusions and the future developing direction are prescribed.